2021
DOI: 10.1111/ppc.12731
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of nursing students' individual characteristics and psychological resilience in psychological distress

Abstract: Purpose This study aims to determine the predictive role of nursing students' individual characteristics and psychological resilience in psychological distress. Design and Methods This study is a descriptive cross‐sectional study. The study sample included 652 nursing students. Binary logistic regression analysis was used for analysis. Findings It has been determined that 65.3% of nursing students have psychological distress. Having a chronic disease, being a woman, poor academic success, choosing the professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The participants' psychological resilience score was high, which was consistent with the research by Serçe et al . (2021), showing that the objects of this study possessed good adaptability in daily life. Furthermore, the participants' positive coping styles score was higher than negative coping styles, which was similar to the research by Pelekanakis et al .…”
Section: Discussionmentioning
confidence: 65%
“…The participants' psychological resilience score was high, which was consistent with the research by Serçe et al . (2021), showing that the objects of this study possessed good adaptability in daily life. Furthermore, the participants' positive coping styles score was higher than negative coping styles, which was similar to the research by Pelekanakis et al .…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, resilience was addressed as contributing to health conditions and well‐being in nursing students (Chow et al, 2018 ; Eaves & Payne, 2019 ; Elzohary et al, 2017 ; Hamadeh Kerbage et al, 2021 ; Ríos‐Risquez et al, 2016 ; Serçe et al, 2021 and Spurr et al, 2021 ). Moreover, resilience was connected to the personal growth of nursing students, as they can learn from overcoming adversities and gain a positive outlook for their future (Hasson et al, 2021 ; Liang et al, 2019 ; Lopez et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resilience can not only be affected by various factors, as described in the previous section, but it can also influence nursing students' health and education. For instance, several studies have shown that nursing students' well‐being is affected by resilience (Abiola et al, 2017 ; Chow et al, 2018 ; Hasson et al, 2021 ; Kim, 2019 ; Kim et al, 2021 ; Labrague, 2021 ; Ríos‐Risquez et al, 2016 ; Serçe et al, 2021 ; Smith & Yang, 2017 ; Spurr et al, 2021 ). Perceived stress was another factor shown to be affected by resilience among nursing students during their nursing education (Drach‐Zahavy et al, 2021 ; Elzohary et al, 2017 ; Kim et al, 2021 ; Lekan et al, 2018 ; Sahu et al, 2019 ; Sam & Lee, 2020 ; Smith & Yang, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Serçe et al . [ 20 ] have reported the effects of low resilience on psychological distress. Sun et al .…”
Section: Introductionmentioning
confidence: 99%